SUSTAINABLE MANUFACTURING CONCEPTS: A LITERATURE REVIEW - Pathak, Priyanka; Singh, M.P. (International Journal of Engineering Technologies and Management Research, 2017)
Purpose – The purpose of this article is to review of literature on Sustainable Manufacturing Concepts. Method – Several frameworks are explored and discussed. Articles on the subject were searched and retrieved, and a content analysis was carried out. Their relationships include correlation, overlapping area, difference, integration and classification based on Sustainable Manufacturing Concepts dimensions. Total 78 research papers have been reviewed for the research contribution, methodologies, country of research, year of publication and different concepts of relevance. Results – This paper identifies major research gaps for sustainable manufacturing concepts through various aspects, thus allowing researchers to identify research opportunities. This paper provides a quantitative descriptive analysis and qualitative thematic analysis to provide an analysis on Sustainable Manufacturing Concepts. Conclusion – Many literature reviews that aim at discussions regarding sustainable manufacturing concepts but none of them focused exclusively on analysis of SM concepts through identification of various factors. Another unique feature of this paper is that total 78 key research papers have been reviewed. The time span taken for this review is about 24 years (1993-2016).